A cohort study of the association between maternal serum Inhibin-A and adverse pregnancy outcomes: A population-based study - Wannaporn Singnoi (2019)
© 2019 The Author(s). Background: To compare the rates of adverse pregnancy outcomes between women with normal and abnormal inhibin-A levels. Methods: Based on a prospective database of Down syndrome screening program, the consecutive records were comprehensively reviewed. Pregnancies were classified into three groups: normal, high (> 2 MoM) and low (< 0.5 MoM) inhibin-A levels. The pregnancies with medical diseases, chromosome abnormalities and fetal anomalies were excluded. The primary outcomes were the rates of preterm birth, preeclampsia, and fetal growth restriction (FGR). Results: Of 6679 recruited pregnancies, 5080 met the inclusion criteria, including 4600, 205 and 275 pregnancies in the group of normal, high, and low inhibin-A levels respectively. The rates of preterm birth, preeclampsia and FGR were significantly higher in the group of high levels; (RR, 1.51, 95%CI: 1.01-2.26; 3.47, 95% CI: 2.13-5.65; 3.04, 95% CI: 1.99-4.65 respectively), whereas the rates of other adverse outcomes were comparable. However, the rate of spontaneous preterm birth among women with high inhibin-A was not significantly increased. Based on multivariate analysis, the preterm birth rate was not significantly associated with inhibin-A levels, but it was rather a consequence of preeclampsia and FGR. Low levels of serum inhibin-A were not significantly associated with any adverse outcomes. Conclusions: High levels of maternal serum inhibin-A in the second trimester are significantly associated with abnormal placentation, which increases the risk of preeclampsia and FGR with a consequence of indicated preterm birth but not a risk of spontaneous preterm birth. In contrast, low inhibin-A levels were not associated with any common adverse pregnancy outcomes.